Flow battery electroanalysis 3: online kinetics measurements using ultramicroelectrodes in channel flow. Issue 26 (21st June 2022) - Segel, Becca; Parr, Zachary; Sawant, Tejal V.; Yim, Carissa S.; Miller, Dean M.; Henry, Thomas J.; McKone, James R.
Abstract : Integrating an analytical cell, based on a channel-flow microelectrode architecture, into the flow loop of a redox flow battery enables continuous measurements of kinetic and thermodynamic properties in real time. Abstract : Redox flow batteries are attractive for grid-scale energy storage, but ongoing work on materials discovery is hampered by the difficulty of measuring electron-transfer rates under battery-relevant conditions. We have developed an experimental approach for collecting continuous voltammetric measurements of flow battery electrolytes by placing a 3-electrode cell containing an ultramicroelectrode into the flow loop of a functioning redox flow battery. We further developed an empirical approach for extracting electron-transfer rate constants from each voltammetric cycle, thereby enabling continuous measurements as a function of state of charge and cycle time. Benchmarking these approaches with iron-based aqueous flow battery electrolytes using platinum and carbon fiber ultramicroelectrodes yielded rate constants that varied in the order Pt > electrochemically oxidized carbon > pristine carbon, in good agreement with prior work. We also found that Pt electrodes become more catalytically active upon cycling for several hours, whereas carbon fiber electrodes with and without oxidative pretreatments remained stable over the same interval. We expect these experimental approaches can be used to measure kinetics and other figures of merit for most electrodes and electrolytes of interest for redox flow batteries as well as in other systems where it is useful to evaluate the properties of a flowing electrolyte in real time.